Feasibility assessment of biogas production from the anaerobic co-digestion of cheese whey, grease interceptor waste and pulped food waste for WRRF. (1st September 2022) - Bolen, T.J.; Hasan, Mahmudul; Conway, Timothy; Stéphane Yaméogo, Djigui David; Sanchez, Pablo; Rahman, Arifur; Azam, Hossain
Abstract: This study investigates the impact of co-digestion of waste activated sludge (WAS) and primary sludge (PS) with cheese whey (CW), grease interceptor (GI) waste, and pulped food waste (PFW) using lab-scale mesophilic anaerobic digesters (AD) and bench-scale biogas potential assays. The addition of CW (20% v/v) and GI waste (10% v/v) with PS resulted in the increase of biogas productions (methane) by 15% and 2%, respectively compared to PS digestion only. The corresponding VS removal increased by 92% and 5% for CW and GI waste addition, respectively. Results from biogas potential assay experiments indicated that CW co-digestion with PS did not improve biogas productions but GI waste and PFW have the potential for improved biogas productions when mixed with PS. The experimental data were further used for detailed energy balance analysis of a water resource recovery facility (WRRF) to understand the influence of co-digestion on energy neutrality. Highlights: Anerobic co-digestion was evaluated for cheese whey (CW), grease interceptor (GI) and pulped food waste (PFW). GI waste showed higher biogas potential in lab-scale anaerobic digester experiments. PS + GI and PS + PFW indicated higher biogas potential during bench-scale experiments Microorganisms has long (>30 days) lag period for GI digestion process. WRRF can gain energy neutrality using CAS system integrated with anaerobic co-digestion.